Letter (copy) : Sandals for Basque Children - Tewson, Vincent
1938-10-18 038-0116-003 Secretary's. HVT/FC/63 18th October, 1938. Mr. Newman, The Co-operative Wholesale Society Ltd., Leman Street, E.C. Dear Mr. Newman, SANDALS FOR BASQUE CHILDREN. Referring to my telephone conversation with you the other day I should be very glad if you could arrange for crepe soled sandals in the following sizes to be sent to the Basque Children's Home, Rowley Lodge, Arkley, Near Barnet, Herts., the cost to be debited against the fund so kindly placed at our disposal by the Co-operative Wholesale Society. The sizes in question are as follows:- Girls. Boys. 2 pairs size 13. 1 pair size 12. 1 pair " 1. 1 " " 13. 3 pairs " 2. 1 " " 1. 7 " " 4. 2 pairs " 2. 2 " " 4½ 1 pair " 3. 2 " " 5. 3 pairs " 4. 4 " " 6. 1 pair " 5. 3 pairs " 6. 2 " " 7. 1 pair " 8. Yours sincerely, 292/946/38/117(II)